Transcriptome analysis provides new insights into cold adaptation of corsac fox (Vulpes Corsac). Issue 4 (19th April 2022) - Yang, Xiufeng; Sun, Guolei; Xia, Tian; Cha, Muha; Zhang, Lei; Pang, Bo; Tang, Qingming; Dou, Huashan; Zhang, Honghai
Abstract: Vulpes are widely distributed throughout the world and have undergone drastic physiological and phenotypic changes in response to their environment. However, little is known about the underlying genetic causes of these traits, especially Vulpes corsac . In this study, RNA‐Seq was used to obtain a comprehensive dataset for multiple pooled tissues of corsac fox, and selection analysis of orthologous genes was performed to identify the genes that may be influenced by the low‐temperature environment. More than 6.32 Gb clean reads were obtained and assembled into a total of 173, 353 unigenes with an average length of 557 bp for corsac fox. Selective pressure analysis showed that 16 positively selected genes (PSGs) were identified in corsac fox, red fox, and arctic fox. Enrichment analysis of PSGs showed that the LRP11  gene was enriched in several pathways related to the low‐temperature response and might play a key role in response to environmental stimuli of foxes. In addition, several positively selected genes were related to DNA damage repair ( ELP2 and CHAF1A ), innate immunity ( ARRDC4 and S100A12 ), and the respiratory chain ( NDUFA5 ), and these positively selected genes might play a role in adaptation to harsh wild fox environments. The results of common orthologous gene analysis showed that gene flow or convergent evolution might be an important factor in promoting regional differentiation of foxes. Our study provides a valuable transcriptomic resource for the evolutionary history of the corsac fox and the adaptations to the extreme environments. Abstract : Assembled and characterized the first transcriptome data for the corsac fox using RNA‐Seq technology and revealed candidate genes LRP11 and several pathway that might be involved in cold environment adaption in foxes.